Ekoteologi Islam dan Pendidikan Kritis Muhammadiyah: Menimbang Keadilan Ekologis di Tengah Industri Ekstraktif - Baiquni, Ahmad (JOURNAL SAINS STUDENT RESEARCH, 2026)
The ecological crisis in mining regions demonstrates that environmental degradation is not merely a technical problem of industrial operations, but also reflects a crisis of ecological awareness and social injustice. The expansion of extractive industries in Southeast Sulawesi has accelerated environmental degradation, polluted natural resources, and undermined the sustainability of local communities. This article aims to examine the role of Islamic ecotheology and Muhammadiyah’s critical education in addressing ecological justice amid the dominance of extractive industries. Employing a qualitative approach through library research, this study analyzes scholarly works on Islamic ecotheology, ecological jurisprudence, critical consciousness education, and Muhammadiyah’s environmental da‘wah. Data are examined using content analysis and a critical-reflective approach to explore the relationship between the principles of tawḥīd, human stewardship (khilāfah), and the socio-ecological realities of mining-affected communities. The findings indicate that Muhammadiyah’s Islamic ecotheology provides a strong normative foundation for viewing nature as a divine trust, while critical education functions as a transformative instrument for fostering moral courage and environmental advocacy. The integration of education, ecological da‘wah, and social movements positions Muhammadiyah as a strategic actor in promoting ecological justice. This study underscores the importance of strengthening critical ecological education grounded in progressive Islamic values to balance economic development, environmental sustainability, and social justice within extractive industrial contexts.